2012
DOI: 10.1371/journal.pone.0046248
|View full text |Cite
|
Sign up to set email alerts
|

A Bacillus Flagellar Motor That Can Use Both Na+ and K+ as a Coupling Ion Is Converted by a Single Mutation to Use Only Na+

Abstract: In bacteria, the sodium ion (Na+) cycle plays a critical role in negotiating the challenges of an extremely alkaline and sodium-rich environment. Alkaliphilic bacteria that grow optimally at high pH values use Na+ for solute uptake and flagellar rotation because the proton (H+) motive force is insufficient for use at extremely alkaline pH. Only three types of electrically driven rotary motors exist in nature: the F-type ATPase, the V-type ATPase, and the bacterial flagellar motor. Until now, only H+ and Na+ ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 51 publications
4
60
0
Order By: Relevance
“…Terahara et al (7) reported that MotPS of B. alcalophilus is the stator driven by Rb + , K + , and Na + , whereas the Met33Leu mutant (equivalent of residue 43 in E. coli) on MotS selectively uses Na + . H + -driven motors commonly have Val at the equivalent positions of MotB, and Na + -driven motors have Leu instead, such as in V. alginolyticus.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Terahara et al (7) reported that MotPS of B. alcalophilus is the stator driven by Rb + , K + , and Na + , whereas the Met33Leu mutant (equivalent of residue 43 in E. coli) on MotS selectively uses Na + . H + -driven motors commonly have Val at the equivalent positions of MotB, and Na + -driven motors have Leu instead, such as in V. alginolyticus.…”
Section: Significancementioning
confidence: 99%
“…In addition, Vibrio alginolyticus has a polar flagellum powered by sodium ions (6). Bacillus alcalophilus has motors driven by rubidium (Rb + ), potassium (K + ), and sodium ions (Na + ) that can be converted to Na + -driven motors by a single mutation (7).…”
mentioning
confidence: 99%
“…The motP/motS genes are universally located down-stream of the ccpA gene, which encodes a central regulator of carbon metabolism in Bacillus species and other Gram-positive organisms (Moreno et al, 2001;Ito et al, 2011). As an exception, extremely alkaliphilic Bacillus alcalophilus Vedder 1934 has a MotP/MotS type stator which utilizes Na + , K + and Rb + as the coupling ions for flagellar rotation (Terahara et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a nonselective member of this family was characterized from Bacillus alcalophilus (Ns V Ba: nonselective voltage‐gated B. alcalophilus ) (14). This channel exhibits a unique selectivity filter (sequence: TLDSWGSG) which conducts K + as well as Na + ions, an adaptation that allows B. alcalophilus to grow in high‐K + conditions (15). Crystal structures from the full‐length bacterial channels Na V Ab and Na V Rh exhibit voltage sensors in partially and fully activated states (7, 9).…”
mentioning
confidence: 99%